EVALUATION OF THE LEARNING PROCESS OF ISLAMIC EDUCATION IN THE IMPLEMENTATION OF CURRICULUM 2013 IN MALUKU TENGAH - St. Jumaeda (al-Iltizam: Jurnal Pendidikan Agama Islam, 2019)
This research was conducted to obtain information about the learning process of Islamic education at the high school in Maluku Tengah. In this study applied a method of evaluation studies Program, collection of data obtained through the study of documents, interviews, questionnaires and observation. The data is then classified into the category of excellent, good, sufficient, less, and very less, based on standards that have been set. The findings in the evaluation of the learning program at Islamic Education for high school in Maluku Tengah district, shows that the quality of the learning process, including both categories. The learning process is determined by the element or the following aspects; (1) the Teacher's performance is judged by category, with the acquisition of average score 4.14 or 82.79% of the maximum score, (2) Learning Facilities are assessed either by obtaining the average score of 3.71 or 74.17% of the maximum score, (3) Climate class is rated good with the acquisition of the mean score of 3.61 or 72.04% of the maximum score. (4) the attitude of the learners are assessed either by obtaining the average score 4.01 or 80.09% of the maximum score. (5) the learning motivation of learners assessed either by obtaining the average score or 77.71 3.88% of the maximum score. So based on the results of the assesment and the categorisation then determined that the quality of the learning process the Islamic education judged included on the category either, with the acquisition of the average score or 3.88 77.50% of the maximum score.